Special meal of the Acehnese, Indonesia during Ramadhan (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Manan A, Salasiyah CI, Rahmawati S, Saprijal, Khairisman, Chairunnisak. 2022. Special meal of the Acehnese, Indonesia during Ramadhan. Biodiversitas 23: 1187-1195. Ie Bu Peudah is a special meal of Acehnese, Indonesia society in every month of Ramadhan consisting of 44 kinds of mixed substances. All mixed ingredients are pounded or mashed using a special mortal done together and collectively. This study aimed to explore more deeply the origin of the making Ie Bu Peudah, its usefulness, social functions, and knowledge transfer amongst community. This descriptive analysis study employed observation, interview, questionnaire, and documentation to collect the data. The obtained data were analyzed by reducing, displaying, and concluding stages. The findings showed that the history of Ie Bu Peudah was carried by Indian traders that visited Aceh then the meal was recreated and modified by the local people in the sultanate of Aceh during 15 AD and was passed down over generations until today. Its efficacy was for body immunity, including the danger of coronavirus and healing many diseases like a tumor as it contains antioxidants, antibiotics, antiseptic, etc. Besides protecting from many diseases, Ie Bu Peudah also has the social functions which were to strengthen the friendship (silaturrahmi) among traditional figures and local people, strengthening the unity, glorifying the month full of blessing, preserving the harmony between the leaders of the village and people and upholding the values of togetherness during the month of Ramadhan.
Keywords: Aceh Besar, Acehnese people, Ie Bu Peudah, special food of Ramadhan